Chinese English as a Foreign Language Teachers’ Immunity and Mindfulness as Predictors of Their Work Engagement - Li, Shengji (Frontiers in Psychology, 2022)
Considering the significant contribution of teachers’ professional triumph in the prosperity of students, the current study aimed to investigate the existence of any relationship among three factors influencing teachers’ success: immunity, mindfulness, and engagement. Furthermore, we attempted to investigate whether EFL teachers’ immunity and mindfulness can predict their work engagement. To this end, a Liker-scale questionnaire including items on teacher immunity, mindfulness, and work engagement was distributed to 582 EFL teachers in China through the WeChat application by employing a convenient sampling. To analyze the collected data, the Spearman Rho correlation index and linear multiple regression analysis were employed. The findings were an indication of a direct relationship among EFL teachers’ immunity, mindfulness, and work engagement. Also, it is found that immunity and mindfulness could predict EFL teachers’ work engagement. The finding of the current study implies the necessity of training and language teachers to cope with the EFL context adversities.